Designing English Folktales Comic Strip as an Interactive Learning Media in SMPN 2 Negara - Ismi Ilyasa; Aditya Ridho Fatmawan; Ni Putu Artila Dewi; Kadek Lina Kurniawati; Isyarotullatifah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to develop an English folklore comic strip as an interactive learning medium for students of SMPN 2 Negara by utilizing Gemini and Canva in the development process. This study used the Research and Development (R&D) method which includes the stages of needs analysis, design, development, implementation, and product evaluation. Data were collected through observation, interviews, documentation, and questionnaires to obtain information on user needs and the quality of the developed media. Data were analyzed descriptively qualitatively and quantitatively to evaluate the feasibility and characteristics of the product. The results showed that Gemini helped generate story ideas, dialogue, and narratives, while Canva supported the systematic arrangement of comic panels, illustrations, captions, and speech bubbles. The resulting comic strip integrated local folklore, moral values, and environmental themes, making it more contextual and culturally relevant. Furthermore, the combination of visual and verbal elements can increase student motivation, engagement, understanding, and creativity. Thus, English-language folklore comic strips have the potential to be an effective interactive learning medium while also supporting the preservation of local culture.